Accuracy and precision of non-invasive thermometers compared with the pulmonary artery temperature: a cross-sectional study - Carvalho, Rafael Lima Rodrigues de; Victoriano, Mariana Avendanha; Campos, Camila Claúdia; Vassallo, Paula Frizera; Nobre, Vandack; Ercole, Flávia Falci (São Paulo Medical Journal, 2025)
BACKGROUND: Temperature fluctuations are critical indicators of a patient’s condition in intensive care units (ICUs). While invasive methods offer a more reliable measurement of core temperature, they carry greater risks of complications, limiting their use in most situations. This underscores the need for research evaluating the reliability of non-invasive temperature monitoring methods. OBJECTIVES: This study aimed to assess the accuracy and precision of four non-invasive temperature measurement techniques compared to pulmonary artery temperature, considered the gold standard. DESIGN AND SETTING: We conducted a cross-sectional clinical study with repeated measures in the ICUs at Hospital das Clínicas da Universidade Federal de Minas Gerais and Hospital Felício Rocho, Belo Horizonte, Brazil. METHODS: All patients admitted with a pulmonary artery catheter were included. We simultaneously recorded temperatures from the pulmonary artery, axillary area, oral cavity, temporal artery, and tympanic membrane. Bland-Altman plots were employed to assess the agreement between the different temperature measurements. RESULTS: A total of 48 patients participated, with a mean age of 54 years. Females comprised 66.67% of the sample. Compared to pulmonary artery temperature, the accuracy and precision (mean and standard deviation) of the non-invasive methods were: axillary (-0.42°C, 0.59°C), oral (-0.30°C, 0.37°C), tympanic membrane (-0.21°C, 0.44°C), and temporal artery (-0.25°C, 0.61°C). Notably, in patients with abnormal body temperature (non-normothermic), only oral and tympanic membrane methods maintained their accuracy and precision. CONCLUSIONS: The non-invasive thermometers evaluated in this study demonstrated acceptable accuracy and precision (within the clinically relevant threshold of 0.5°C) compared to pulmonary artery temperature. Among the non-invasive methods, the tympanic membrane measurement proved to be the most reliable, followed by the oral method.